Cognitive radio oriented wireless networks : 11th International Conference, CROWNCOM 2016, Grenoble, France, May 30-June 1, 2016, Proceedings /: 11th International Conference, CROWNCOM 2016, Grenoble, France, May 30-June 1, 2016, Proceedings. (2016) - Unknown
No abstract available